Factors affecting the adoption of livestock insurance among dairy farmers in Dang district, Nepal - Timsina, Tirth Kumar; Tiwari, Ujjal (Journal of Agriculture and Natural Resources, 2024)
The dairy sector plays an important role in food and nutrition security of rural households. Dairy business is exposed to high risks. The insurance scheme provides to avert the unanticipated economic loss of dairy farms. This study was conducted to analyze the various factors affecting livestock insurance adoption among dairy farmers in Dang district, Nepal. Required information was obtained through farm household surveys, focus group discussions (FGDs), and key informant interviews (KIIs). The effect of twelve predictor variables on the adoption of livestock insurance was assessed using logit regression model. This study was conducted in three local levels of Dang district in September 2020. Ninety dairy animal insurers were surveyed as a household through a stratified random sampling method. A semi-structured questionnaire was developed for the household interview, six key informant surveys, and three focus group discussions. The collected data were analyzed through logit regression model using Stata software. The regression results revealed that the probability of insurance adoption significantly increases with technical support (p=0.001), loan taken (p=0.049), breed type (p=0.0001), experience in livestock (p=0.001) and membership in the organization (p=0.011). The education status of farmers, own grazing land, access to media were found influencing factor for adoption of the livestock insurance.